Perception and Preventive Behaviour about COVID-19 Pandemic among the Members of a Selected Cantonment in Bangladesh - Irfan, SM Nurul; Mithun, Sangita; Abbas, Md Golam (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Appropriate knowledge, attitude and practice against any infectious disease improve perception and consequently adopt preventive practices toward disease transmission. Good perception and preventive practice is the key to prevent infectious disease like COVID-19. Objective: To assess the perception and protective behaviour against COVID-19 among the members of Shaheed Salahuddin Cantonment, Ghatail. Materials and Methods: This cross-sectional study was conducted at Shaheed Salahuddin Cantonment from March 2022 to May 2022 among conveniently selected 1315 respondents. Data were collected through face-to-face interview using a pretested semi-structured questionnaire. Results: The majority (79.8%) of the respondents were male, residing in the sainik line (72.3%) having monthly income of <15000 taka. Three-fourth of the respondents were lance corporal/sainik, 30.8% were currently married having secondary school certificate level of educational qualification. Study revealed that more than two-third (62.5%) respondents had moderate perception about COVID-19 and about 87.3% respondents showed good preventive behaviour. Preventive behaviour is significantly associated with male gender (χ2=2.49; p < .05), lower age group (<20 years) respondents (χ2=9.93, p < .05) who were qualified in secondary school certificate education (χ2=8.54, p<.05), married (χ2=4.97, p < .05), stayed in sainik line (χ2=9.19, p<.05) and in lance corporal/sainik respondents (χ2=13.12, df =4, p =.01) Conclusion: Extensive health education program should be undertaken to create good perception and preventive behaviour among susceptible respondents like female gender, aged, unmarried respondents of Shaheed Salahuddin Cantonment. JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 80-85